Evaluación de una plantación de Carapa guianensis “andiroba”, en la parcela n° 4 del CIEFOR - Puerto Almendra, Loreto – Perú. 2022 - Vela Silva, Jenifer Thalia (2023)
The objective of the study was to determine the increase in diameter and height of Carapa guianensis plants in Forest Plot No. 4 of CIEFOR – Puerto Almendras, in a 3-year-old under-canopy plantation. The average increase in diameter of the 171 plants evaluated was 5,2 mm, while the average increase in height was 14,6 cm. Survival averaged 87% and mortality reached 13% in the plot. GOOD quality plants with 94 seedlings that represented 54,97 liters of the total seedlings evaluated followed by REGULAR quality with 68 live samples showing 39,67% and finally low quality samples were observed. with 9 seedlings representing a total of 5,26%. Plant quality by quality factor ranges from fair to good. Likewise, it is recommended to carry out periodic evaluations in plot No. 4 of C. guianensis.